2018
DOI: 10.1016/j.chest.2018.08.1058
|View full text |Cite
|
Sign up to set email alerts
|

Randomized, Double-Blind, Placebo-Controlled, Phase 2 Trial of BMS-986020, a Lysophosphatidic Acid Receptor Antagonist for the Treatment of Idiopathic Pulmonary Fibrosis

Abstract: ClinicalTrials.gov; No.: NCT01766817; URL: www.clinicaltrials.gov.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
112
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 152 publications
(112 citation statements)
references
References 11 publications
0
112
0
Order By: Relevance
“…In patients with idiopathic pulmonary fibrosis, LPAR antagonists led to a significant rate of decline in disease progression. Although the LPAR antagonist was well tolerated in most patients, elevations of hepatic transaminases and ALP were detected in some patients [72]. Together these data indicate that antagonizing LPAR signaling may offer an interesting therapy for AVS.…”
Section: Future Perspectivementioning
confidence: 84%
“…In patients with idiopathic pulmonary fibrosis, LPAR antagonists led to a significant rate of decline in disease progression. Although the LPAR antagonist was well tolerated in most patients, elevations of hepatic transaminases and ALP were detected in some patients [72]. Together these data indicate that antagonizing LPAR signaling may offer an interesting therapy for AVS.…”
Section: Future Perspectivementioning
confidence: 84%
“…Lysophosphatidic acid (LPA) is an important profibrotic mediator that signals though its receptor LPA 1 to promote vascular leak and fibroblast recruitment (88). The LPA/LPA 1 pathway contributes to the development of fibrosis across multiple human disease processes (88)(89)(90)(91)(92), and a phase II clinical trial of an LPA 1 receptor antagonist in IPF demonstrated a reduction in the degree of pulmonary function decline in the treatment arm (93). 11 C-BMT-136088, a PET radioligand for the LPA 1 receptor (94), has been used in rhesus monkeys to determine LPA 1 receptor expression in the lungs and other organs, volume of drug distribution, and amount of LPA 1 receptor antagonist needed to block half of the receptor uptake of the PET probe (94).…”
Section: Assessing Target Expression and Confirming Target Engagementmentioning
confidence: 99%
“…A phase 2a randomised placebo‐controlled trial with GLPG1690 showed favorable stability of FVC (although not sufficiently powered) compared to placebo with good safety profile . BMS‐986020, an LPA receptor antagonist, has demonstrated a slower rate of FVC decline in a recent Phase 2 double‐blinded randomised control trial . Another novel drug PBI‐4050 targeting transforming growth factor 1 β (TGF‐1β), connective tissue growth factor (CTGF) and cytokines IL‐23p19 and IL‐6 has successfully navigated a Phase 2 trial of safety and efficacy with no concerns reported .…”
Section: Future Directionmentioning
confidence: 99%
“…72 BMS-986020, an LPA receptor antagonist, has demonstrated a slower rate of FVC decline in a recent Phase 2 double-blinded randomised control trial. 73 Another novel drug PBI-4050 targeting transforming growth factor 1 b (TGF-1b), connective tissue growth factor (CTGF) and cytokines IL-23p19 and IL-6 has successfully navigated a Phase 2 trial of safety and efficacy with no concerns reported. 74 This trial allowed concurrent use of either pirfenidone or nintedanib with stable FVC (over a 12-week period) reported in both PBI-4050 alone and PBI-4050/nintedanib but reduced in PBI-4050/pirfenidone cohort.…”
Section: Future Directionmentioning
confidence: 99%